Temporal and spatial distribution of plankton community in three Indonesian salt pond environments - RINI SUSILOWATI; DIETRIECH G. BENGEN; MAJARIANA KRISANTI; HEDI INDRA JANUAR; IMAN RUSMANA (Society for Indonesian Biodiversity, 2023)
Abstract. Susilowati R, Bengen DG, Krisanti M, Januar HI, Rusmana I. 2023. Temporal and spatial distribution of plankton community in three Indonesian salt pond environments. Biodiversitas 24: 1833-1844. Plankton is a biological community that plays an important role in biological systems during salt crystallization. The correlation between plankton communities and water quality parameters was examined in three salt pond center areas (Brebes, Tuban, and Sampang). The values of nutrient content in Brebes were higher compared to other locations, with phosphate (5.38-5.66 mg/L), nitrate (0.17-0.74 mg/L), nitrite (0.07-0.1 mg/L), and total organic matter (0.03-0.07 mg/L). Based on multivariate analysis, there was no significant difference in the abundance of plankton among the three salt pond locations. Furthermore, Spearman's correlation test indicated a negative correlation (Sig<0.05) between salinity and the abundance and diversity of plankton. The highest abundance of phytoplankton (127,721±11.227 cells/L) and zooplankton (3,339±391 idvs/L) was found in the Brebes. Phytoplankton from the genera Bacillarophyceae Bacillarophyceae was dominant in the three locations. In Brebes and Sampang, the dominant classes of zooplankton were Litostomatea, whereas, Oligotrichea was dominant in Tuban, The phytoplankton community structure has a diversity index (H') of 0.91-2.05, and Evenness index (E) ranging from 0.12-0.20, and a dominance index (C) showing a level of 0.14-0.34. At the same time, the zooplankton community has a diversity index (H') of 0.81-1.64, an evenness index (E) that has ranged from 0.18-0.22, and a dominance index (C) that has ranged from 0.03-0.20. The research examines plankton communities in varying salinity and their response to environmental changes. This data is useful for managing salt pond productivity, vital for sustainable and high-quality salt production.